2007
DOI: 10.1110/ps.062730007
|View full text |Cite
|
Sign up to set email alerts
|

Conductance and amantadine binding of a pore formed by a lysine‐flanked transmembrane domain of SARS coronavirus envelope protein

Abstract: The coronavirus responsible for the severe acute respiratory syndrome (SARS-CoV) contains a small envelope protein, E, with putative involvement in host cell apoptosis and virus morphogenesis. It has been suggested that E protein can form a membrane destabilizing transmembrane (TM) hairpin, or homooligomerize to form a regular TM a-helical bundle. We have shown previously that the topology of the a-helical putative TM domain of E protein (ETM), flanked by two lysine residues at C and N termini to improve solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
189
3
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 168 publications
(204 citation statements)
references
References 27 publications
10
189
3
2
Order By: Relevance
“…This possibility was originally addressed using computational modeling, which predicted that the E protein HD could form stable dimers, trimers, and pentamers [62]. This prediction was further bolstered by several spectroscopic studies, which showed that the HD of SARS-CoV E forms a pentamer [63,64,65]. However, this result has not been confirmed for the other E proteins, or for the full length SARS-CoV E protein in a natural membrane.…”
Section: The Ion Channel Activity Of Cov Ementioning
confidence: 99%
“…This possibility was originally addressed using computational modeling, which predicted that the E protein HD could form stable dimers, trimers, and pentamers [62]. This prediction was further bolstered by several spectroscopic studies, which showed that the HD of SARS-CoV E forms a pentamer [63,64,65]. However, this result has not been confirmed for the other E proteins, or for the full length SARS-CoV E protein in a natural membrane.…”
Section: The Ion Channel Activity Of Cov Ementioning
confidence: 99%
“…SARS-CoV E protein has been shown unequivocally to have just one TM domain , and is the only E protein for which structural data is available Pervushin et al, 2009). E proteins have been shown to form ion channels in synthetic membranes (Torres et al, 2007;Wilson et al, 2006), with reported conductance of 20-30 pS. However, characterization with properly purified full length and transmembrane peptides of SARS-CoV E protein has produced much higher (>10 times) conductances Verdia-Baguena et al, 2012, 2013a.…”
Section: Introductionmentioning
confidence: 99%
“…In Coronaviridae, it was demonstrated that the envelope (E) proteins of MHV, SARS-CoV, HCoV-229E and IBV exhibit viroporin activity [35,37,38,[100][101][102][103]. The E protein of SARS-CoV is 76 amino acids long, contains one predicted TM domain and forms a pentameric ion channel [35,36,103,104]. The SARS-CoV E protein is more selective for Na + than for K + ions, status similar to that of Alphavirus 6 K proteins [11].…”
Section: Coronavirus E and 3amentioning
confidence: 99%